2022
DOI: 10.1021/acsami.2c03151
|View full text |Cite
|
Sign up to set email alerts
|

Local Epitaxial Templating Effects in Ferroelectric and Antiferroelectric ZrO2

Abstract: Nanoscale polycrystalline thin-film heterostructures are central to microelectronics, for example, metals used as interconnects and high-K oxides used in dynamic random-access memories (DRAMs). The polycrystalline microstructure and overall functional response therein are often dominated by the underlying substrate or layer, which, however, is poorly understood due to the difficulty of characterizing microstructural correlations at a statistically meaningful scale. Here, an automated, high-throughput method, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, up to date, most of the HZO thin films studied were polycrystalline, which contained secondary non-ferroelectric phases that suppressed the ferroelectric properties and obscured the understanding of the fundamental physics of ferroelectric HZO 17,33,34 . It was demonstrated that the ferroelectric orthorhombic phase can be stabilized in epitaxial HZO films grown on a perovskite substrate [35][36][37][38][39][40][41] . Notably, it was found that the La 0.67 Sr 0.33 MnO 3 (LSMO) buffer layer is essential in the epitaxial growth of ferroelectric HZO 18,19,36,42 .…”
mentioning
confidence: 99%
“…However, up to date, most of the HZO thin films studied were polycrystalline, which contained secondary non-ferroelectric phases that suppressed the ferroelectric properties and obscured the understanding of the fundamental physics of ferroelectric HZO 17,33,34 . It was demonstrated that the ferroelectric orthorhombic phase can be stabilized in epitaxial HZO films grown on a perovskite substrate [35][36][37][38][39][40][41] . Notably, it was found that the La 0.67 Sr 0.33 MnO 3 (LSMO) buffer layer is essential in the epitaxial growth of ferroelectric HZO 18,19,36,42 .…”
mentioning
confidence: 99%
“…2c, Extended Data Fig. 4), while also underscoring the important role of amorphous templating in HZO antiferroelectric-ferroelectric phase stability 52,53 .…”
Section: Ultrahigh Energy Storage Via Antiferroelectric Negative Capa...mentioning
confidence: 82%
“…Figure d–f show the in-plane particle size distribution of the film at these three annealing rates. When performing particle size statistics, it is sensible to separately analyze the sizes of particles of m-phase and o-phase and compare them . Further discussion on the particle size of o-phase and m-phase can be found in Figures S6–S7.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S5 demonstrates the significant influence of the oxygen pressure on the interplanar spacing of the orthorhombic phase. The relationship between the interplanar spacing of d o-HZO(111) and p indicates that as the deposition pressure increases from 1 to 15 Pa, the interplanar spacing of d o-HZO decreases from approximately 2.977 to 2.945 Å (by 46 Further discussion on the particle size of o-phase and m-phase can be found in Figures S6−S7. Figure 2d shows that the particle size in the film with the 5 °C/min cooling rate is scattered and distributes in a quite wide range of 6−26 nm; Figure 2e−f show that the particle size becomes smaller and distributes in a narrower range with the increase of annealing rate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%